The influence of non-governing law on the interpretation of contracts in the United States. (2nd September 2015) - Wolters, Pieter
Abstract : In a globalized world, the parties and the contract are often "connected" to a law or jurisdiction that is different from the forum. In the current literature, the question of whether this law should influence the interpretation of such a contract has been approached from a conflict of laws perspective. However, this approach does not explain the influence of the "non-governing" law when this law is not applied. After all, the conflict of laws rule might lead to the application of another law. This paper shows that the non-governing law can influence the interpretation of a contract. Non-governing law can be connected to the contract, or to the parties to the contract, in various ways. In these situations, a court can consider non-governing law to better vindicate the intention of the parties. Furthermore, non-governing law can also influence the interpretation "through" other circumstances. Moreover, the influence of non-governing law is not significantly different from the influence of several more established circumstances. The influence of non-governing law on the interpretation of a contract is limited to situations wherein the relevant conflict of laws rules do not lead to the application of the connected non-governing law. However, within this scope, the ability to consider non-governing law is a useful tool that is superior to the "conflicts of law approach".